Peningkatan Hasil Belajar IPA Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation di Sekolah Dasar - Tembang, Yonarlianto; Harmawati, Diah; Rahajaan, Julinda Priskila (Jurnal Ilmiah Sekolah Dasar, 2019)
The purpose of this study was to improve the learning outcomes of class V students through the application of Cooperative learning models of type group investigation to science subjects at Wasur Merauke Elementary School. The research used was classroom action research (PTK) with a type of collaborative research and carried out in two cycles. Each cycle consists of 4 stages, namely planning, implementation, observation, and reflection and carried out in 3 meetings. The subjects in the study consisted of 26 students consisting of 15 male students and 11 female students. The data analysis technique used is the data analysis of the observation sheet used to determine the feasibility of the learning model and student learning outcomes in science learning. Based on the results of this study, the results of the implementation of the learning model increased in each cycle I by 66.0% in the sufficient category to 72.5% in the second cycle in the good category. While the percentage of completeness of student learning outcomes in the first cycle amounted to 64.4% and in the second cycle the percentage of student learning completeness increased by 80.7%. It can be concluded that by applying the cooperative learning model type group investigation can improve science learning outcomes of fifth grade students of Wasur Merauke Elementary School.